PENGARUH MODEL PEMBELAJARAN BERDIFERENSIASI BERBASIS ETNOMATEMATIKA TERHADAP KEMAMPUAN LITERASI MATEMATIS SISWA - Mulia Dewi; Minta Ito Simamora; Ulfa Annisa Lubis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of ethnomathematics-based differentiated learning model on students' mathematical literacy skills. The study was conducted at Pancasila Tanjung Beringin Private Junior High School in the 2025/2026 academic year with a Posttest-Only Control Group Design. The research sample consisted of 51 students divided into two classes. Class VIII A is the experimental class with 25 students using the differentiated learning model, while class VIII B is the control class with 26 students using the conventional learning model. The research instrument is in the form of essay questions that have been tested for validity and reliability. The results of the analysis show that the average posttest score of the experimental class is 79.00, higher than the control class of 60.14. So, the average difference is 18.86. The prerequisite test shows that the data is normally distributed and homogeneous. The t-test results show that the Sig. (2-tailed) = t_count (5.665) > t_(table) (2.01), and Sig. (2-tailed) = 0.000 < 0.05, it can be concluded that there is a significant average difference between the posttest results of the two classes. The effect size calculation obtained a Cohen's d value of 1.6 in the